Legal Protection Of Children As Perpetrators Of Narcotics Crimes (A Study At The Special Children's Institution Special Institution For Children (LPKA) Class I Medan) - Peni Lestari; Robi Krisna (Best Journal of Administration and Management, 2023)
A child who is the perpetrator of a crime must provide protection for the rights of a child. In the criminal court system for the child who has a role in providing case assistance for children who deal with the law. A child or minor who commits a drug crime can be given special attention to the child in order to provide the best. This research has the aim of knowing the implementation, obstacles and efforts in providing solutions to the obstacles of narcotics crimes committed by children at the Medan Class I Child Special Development Institution in Medan. The research method used is juridical sociology, which emphasizes to obtain empirical hokum by going directly to the object. Based on this research, several research results were found as follows: semestrinya the implementation of the child protection law is handed over to the Child Special Development Institution Class I Medan. The next obstacle is the lack of understanding of law enforcement officials that children, like drug users, are the only victims. The second obstacle is the lack of public understanding of juvenile drug users. Drug use by juveniles is considered the same as drug crimes committed by adults in the public perception. The third obstacle is the weakness in infrastructure, especially in rural areas in Indonesia. Especially in the rehabilitation process, with the mechanism of the rest process, mental rehabilitation, physical rehabilitation, physical development, spiritual development, all of which have not been provided at the Medan Class I Special Child Development Center in Medan.